Production Parameters and Taxonomical Studies of Pseudomonas aeruginosa (MTCC No. 10620) Isolated From Marine Sponge for The Production of Antimicrobial Metabolites - Shamsher Kumar, P.; Radha Krishna, E.; Sujatha, P.; Veerendra Kumar, B. (Asian Journal of Chemistry, 2011)
The culture conditions were optimizing for the production of antimicrobial metabolites by Pseudomonas aeruginosa. The metabolite production was started after 24 h of incubation and reached its maximum levels after 72 h and decreased gradually. The pH was adjusted to 7.0 and temperature to 35 ºC supported the production of antimicrobial metabolites. The best proved carbon and nitrogen sources were sucrose and peptone, respectively as basal medium. The other aim of study was to identify and characterize by its morphological, physiological and biochemical studies and deposited to Microbial Type Culture Collection and Gene bank, IMTECH, Chandigarh, India. Pseudomonas aeruginosa is also mesophilic, alkaliphilic and moderate salt tolerance in nature. It utilize carbon sources like dextrose, galactose, mannitol, xylose, mannose and showed positive results to citrate utilization, casein hydrolysis, cytrochrome oxidase, catalase test, gelatin hydrolysis and arginine dihydrolase. The results indicated that the natural marine environment is also good sources for isolation of novel varieties of antagonistic bacteria.